2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347537
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation- and error-related EEG signals during realistic human-machine interaction: A study on visual and tactile feedback

Abstract: Abstract-The exploitation of EEG signatures of cognitive processes can provide valuable information to improve interaction with brain actuated devices. In this work we study these correlates in a realistic situation simulated in a virtual reality environment. We focus on cortical potentials linked to the anticipation of future events (i.e. the contingent negative variation, CNV) and error-related potentials elicited by both visual and tactile feedback. Experiments with 6 subjects show brain activity consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 19 publications
(25 reference statements)
2
23
0
Order By: Relevance
“…They complement studies showing that these signals are stable across time [4], feedback modalities [13] and experimental protocols [14]. Further work is nonetheless required to demonstrate if this robustness actually translates into more reliable BMI applications.…”
Section: Discussionmentioning
confidence: 53%
“…They complement studies showing that these signals are stable across time [4], feedback modalities [13] and experimental protocols [14]. Further work is nonetheless required to demonstrate if this robustness actually translates into more reliable BMI applications.…”
Section: Discussionmentioning
confidence: 53%
“…The feasibility of performing single-trial recognition of ErrPs has been demonstrated in different paradigms and setups, including P300 spellers [7], Motor-imagery BCI [6], human-robot interaction [9], [8], and car driving [10]. Noticeably these signals, linked to cognitive monitoring processes, have also been reported to be rather stable across different recording days [11], and feedback characteristics [12], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably these signals, linked to cognitive monitoring processes, have also been reported to be rather stable across different recording days [11], and feedback characteristics [12], [9]. As a matter of fact, they are not strongly modulated by the stimulus presentation rate [13], although they may vary depending on factors such as the predictability of the stimulus [14] These studies typically compare the signal across different conditions without assessing the classification performance across different experimental conditions (i.e., generalisation across days or feedback presentation speeds).…”
Section: Introductionmentioning
confidence: 99%
“…This signal, which typically lasts from about 300 ms to several seconds with magnitudes up to 50µV has been termed contingent negative variation (CNV) potential [6].This potential has been linked to the preparatory processing required for appropriate actions at the arrival of future events [7], [8]. Nevertheless, apart from few examples [9], [10], [12], these potentials have been studied using simple procols and stimlui.…”
Section: Introductionmentioning
confidence: 99%